Investigative study on preprint journal club as an effective method of teaching latest knowledge in astronomy - Daryl Joe D. Santos (American Physical Society, 2021)
As recent advancements in physics and astronomy rewrite textbooks in a very rapid pace, there is a growing need in keeping abreast of the latest knowledge in these fields. Reading preprints is one of the effective ways to do this. However, by having journal clubs where people can read and discuss journals together, the benefits of reading journals become more prevalent. We present an investigative study of understanding the factors that affect the success of preprint journal clubs in astronomy, more commonly known as Astro-ph/Astro-Coffee (hereafter called AC). A survey was disseminated to understand how universities and institutions from different countries implement AC. We interviewed 9 survey respondents and from their responses, and we identified four important factors that make AC successful: commitment (how the organizer and attendees participate in AC), environment (how conducive and comfortable AC is conducted), content (the discussed topics in AC and how they are presented), and objective [the main goal(s) of conducting AC]. These four factors are shown to correlate with each other. We also present the format of our AC, an elective class which was evaluated during the Spring semester 2020 (March 2020–June 2020). Our evaluation with the attendees showed that enrollees (those who are enrolled and are required to present papers regularly) tend to be more committed in attending compared to audiences (those who are not enrolled and are not required to present papers regularly). In addition, participants tend to find papers outside their research field harder to read, which makes introducing and explaining basic knowledge without the assumption of the audience already knowing the topic very important. Finally, we showed an improvement in the weekly number of papers read after attending AC of those who present papers regularly, and a high satisfaction rating of our AC. We summarize the areas of improvement in our AC implementation, and we encourage other institutions to evaluate their own AC in accordance with the four aforementioned factors to assess the effectiveness of their AC in reaching their goals.